Stunting and its associated factors among children below five years old in the east coast of Peninsular Malaysia : findings from the national health and morbidity survey 2016 - Haron, Muhammad Zulfahmi (2020)
Stunting is the incapability of the children to achieve their potential height for their age. Stunting is a form of malnutrition belong to the undernutrition group. Children are defined as stunted if their height-for-age value is less than two standard deviations of the World Health Organization Child Growth Standards median. This study was aimed to determine the proportion of stunting among children below five years old and its associated factors in the east coast of Peninsular Malaysia. This study utilised data from the National Health and Morbidity Survey (NHMS) 2016. NHMS is the population-based survey which supplement routinely available data on trends of issues in health, health needs and expenditure in the Malaysian nation. Multiple logistic regression was used to compare between non-stunting and stunting group. The proportion of stunting among children below five years old in this east coast region was 26.2%. When divided by state, the highest proportion of stunting was in Kelantan, which was 28.8% , 26.2% and 23.4% for Pahang and Terengganu, respectively. Factors associated with stunting in this study were children in the age group of 24-59 months (AdjOR; 1.52, 95% CI: 1.26, 1.83), boys (AdjOR; 1.47, 95% CI: 1.23, 1.76), being Orang Asli children (AdjOR, 2.84; 95% CI: 1.86, 4,32), children with low birth weight from 1500 to 2499 grams (AdjOR, 1.86; 95% CI: 1:36, 2:55), and households that practice unsanitary waste disposal (AdjOR; 1.42, 95% CI: 1.16, 1.74). In conclusion, the proportion of stunting among children under the age of five on the east coast of Peninsular Malaysia is high and intervention programs should be intensive and focussed public health program should target these factors to reduce the stunting prevalence in this region.